ASSESSING THE DUAL INFLUENCE OF SOCIAL MEDIA ON MATHEMATICS UNDERGRADUATES’ LEARNING OUTCOMES. (UNIZIK Journal of STM Education, 2025)
This study examined assessing the dual influence of social media on mathematics undergraduates’ learning outcomes. The research provided five research questions and two hypotheses to determine the student activeness on social media in relation to their learning outcome. This study adopted a descriptive survey design. The populations used for this study comprised of all the full-time undergraduate students of mathematics from Tai Solarin University of Education. Using convenience sampling technique, a total sample of one hundred and five respondents were selected across all levels for the study. A self-developed Questionnaire; face validated by experts with reliability coefficient of 0.86 established using Cronbach Alpha, was used for data collection. Also, the students’ academic records were collected from the departments. Data collected for the study was analyzed using Statistical Package for the Social Sciences (SPSS) version 21. Frequency counts, percentage, mean and standard deviation addressed research questions while the hypothesis generated were tested using multiple regression analysis. The findings revealed that WhatsApp is the highest social media students are exposed to follow by Facebook, Instagram, TikTok, Twitter and Snapchat. It was concluded that social media has a dual influence (positive and negative) on students learning outcome. However, to have a more positive learning outcome, it was recommended that social media network usage by students should focus on the academic relevance.
Keywords: Social Media, Dual Influence, Mathematics, Undergraduate, Learning Outcome.